Pembuatan Media Pembelajaran IPA Berbasis Lesson Study di SMPN 16 Mataram - Hikmawati Hikmawati; A Wahab Jufri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
The science learning media available at the Science Laboratory of SMPN 16 Mataram is still incomplete and some are damaged. The purpose of this community service activity is to create learning media based on lesson study at SMPN 16 Mataram. Lesson studies have 3 stages: the plan, do and see stages. At the planning stage, the activity participants are given information about the learning media and the practice of lesson study, after that, it is determined the learning media to be made and the model teacher who will simulate the media in the class. In the do stage, the model teacher simulates the application of instructional media, while the observer observes the activities of the teacher and students. In the see stage, the model teacher describes his experience doing media simulations in the classroom, while the observer provides input and suggestions for improvement in the application of further learning media. The planning phase is carried out on Tuesday, August 6, 2019, while they do and see phase is carried out on Saturday, September 7, 2019. The science learning media produced from lesson study activities according to the agreement on the planning stage consist of a hydraulic system (excavator), alarm earthquake, and portable microscope. The learning media that is simulated for use in the classroom is a portable microscope. The simulation activity of the application of learning media was participated by 30 students of SMPN 16 Mataram, with 4 observers. The making of instructional media with lesson study patterns in community service activities has increased the number of science laboratory equipment at SMPN 16 Mataram.